Theoretical prediction of the punching shear strength of concrete flat slabs under in-plane tensile forces. (15th February 2021) - Fernández, Pablo G.; Marí, Antonio; Oller, Eva
Highlights: A mechanical model for the punching shear strength considering in plane tensile forces. A linear reduction of the punching strength with T/Tcr for moderate tensile forces. High level of tensile forces may produce a reduction of the punching shear strength. The proposed model accurately captures the behaviour of available tests results. Predictions made with existing Code provisions are conservative. Abstract: RC slabs can be subjected simultaneously to transverse loads and in-plane tensile forces, as it happens in top slabs of continuous box girder bridges decks, in the regions of negative moments, or in flat slabs subjected to horizontal loads, produced by wind or earth pressure. Tensile forces can reduce the shear punching capacity of slabs. However, few studies have been carried out to quantify this effect. With this purpose, a mechanical model has been developed to capture the influence of in-plane tensile forces on the punching shear strength and verified with punching tests under different in-plane tensile load levels. The model, presented in this paper, consists of an extension of the Punching shear Compression Chord Capacity Model to account for the effects of tensile forces on the resisting actions. A linear reduction of the punching shear strength as a function of the external load applied has been obtained for moderate tensile forces, whereas high level of tensile forces may produce premature yielding of the reinforcement and further reduction of the punching shear strength. The proposed model accurately captures the available test results, including the effects of the premature yielding of reinforcement when the tensile force produces concrete cracking. In addition, predictions of punching-shear-tensile tests available in the literature were made with different theoretical models included in design codes, which yielded in general conservative results and showed high scatter.